2012
DOI: 10.1093/gbe/evs075
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Demographic History of the Human Lineage Using Whole-Genome Sequences from Human and Three Great Apes

Abstract: The demographic history of human would provide helpful information for identifying the evolutionary events that shaped the humanity but remains controversial even in the genomic era. To settle the controversies, we inferred the speciation times (T) and ancestral population sizes (N) in the lineage leading to human and great apes based on whole-genome alignment. A coalescence simulation determined the sizes of alignment blocks and intervals between them required to obtain recombination-free blocks with a high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
(108 reference statements)
0
23
0
Order By: Relevance
“…These observations are likely to provide a lower mutation rate even with the phylogenetic approach. Indeed, assuming k of 0.012 after excluding indels, N ranging from 59,300 to 122,000 (Hara et al, 2012;, T at 6 million years ago, and a generation time of 20-25 years, I calculated μ as 1.10-1.67 × 10 -8 , which is comparable with the estimates based on high-throughput sequencing (Table 1).…”
Section: Updating Our Understanding Of Mutation Ratesmentioning
confidence: 52%
See 1 more Smart Citation
“…These observations are likely to provide a lower mutation rate even with the phylogenetic approach. Indeed, assuming k of 0.012 after excluding indels, N ranging from 59,300 to 122,000 (Hara et al, 2012;, T at 6 million years ago, and a generation time of 20-25 years, I calculated μ as 1.10-1.67 × 10 -8 , which is comparable with the estimates based on high-throughput sequencing (Table 1).…”
Section: Updating Our Understanding Of Mutation Ratesmentioning
confidence: 52%
“…While the averages of estimated τ HC (= μT HC ) and τ HCG (= μT HCG ), where T HC and T HCG represent speciation times between human and chimpanzee and between the ancestor of human/chimpanzee and gorilla, respectively, varied among the human chromosomes, the averages of τ HC and τ HCG of the human chromosomes were highly correlated (Fig. 1A) (Hara et al, 2012). One simple explanation for this observation is that mutation rates differ across chromosomes through mechanisms that have not yet been clarified (Hara et al, 2012).…”
Section: Heterogeneous Mutation Rate Of Nucle-otides Across the Humanmentioning
confidence: 99%
“…Many studies have proved and identified the genome and information of gorilla (Gibbs and Rogers 2012;Hara et al 2012;Scally and Durbin 2012;Ventura et al 2011;Vigilant and Bradley 2004). Gorilla is in the family of hominidae along with human, orangutan and chimpanzee.…”
Section: Transposable Element Distribution Of Human and Various Primatesmentioning
confidence: 99%
“…In the similar manner to gorillas, chimpanzee is another primate that has analogous DNA to human (Han et al 2007b;Hara et al 2012;Li and Saunders 2005;Liu et al 2009;Olson and Varki 2002;Prüfer et al 2012; The chimpanzee sequencing and analysis consortium 2005; Ventura et al 2011). Chimpanzees are included in the This data are modified from Smit et al 2010.…”
Section: Transposable Element Distribution Of Human and Various Primatesmentioning
confidence: 99%
See 1 more Smart Citation